Epidemiology of eltor cholera in rural Bangladesh: importance of surface water in transmission - Hughes, James M. (1982)
In order to define the role of water used for drinking, cooking, bathing, and washing in the transmission of Vibrio cholerae biotype eltor infections in an area with endemic cholera, surveillance was initiated in neighbourhoods with a culture-confirmed cholera index case and others with index cases with non-cholera diarrhoea as controls. In neighbourhoods with cholera infection, 44% of surface water sources were positive for V. cholerae, whereas only 2% of surface sources were positive in control neighbourhoods. Canals, rivers, and tanks were most frequently positive. There was an increased risk of infection for families using water from culture-positive sources for drinking, cooking, bathing, or washing and for those using water sources used by index families for drinking, cooking or bathing. Analysis of the results for individuals showed that in this case there was an increased risk of infection associated with using water from culture-positive sources for cooking, bathing, or washing, but not with using water from culture-positive sources for drinking. Individuals who used the same water source as an index family for bathing were more likely to be infected than those using different sources. For families drinking from a culture-negative source, there was an association between infection and bathing in a positive source. For families using a different bathing source from the index family there was an association between infection and drinking from the same source as the index family, and for families using a different drinking source from the index family there was an association between infection and bathing in the same source as the index family. These data suggest that use of surface water is important in the transmission of V. cholerae and that, in addition to providing safe drinking water, education regarding the risk of transmission of infection by water from potentially contaminated sources used for other purposes, especially bathing, may also be necessary to control transmission in areas where eltor cholera is endemic.